Binomische Formeln

Die drei binomischen Formeln lauten:

  1. $(a+b)^2=a^2+2ab+b^2$
  2. $(a-b)^2=a^2-2ab+b^2$
  3. $(a+b)\cdot (a-b)=a^2-b^2$

Beispiele

  1. $(2x+5)^2=4x^2+20x+25$
  2. $(3-x)^2=9-6x+x^2$
  3. $(x+2y)\cdot (x-2y)=x^2-(2y)^2$

Herleitung kompakt

  1. Binomische Formel

$(a+b)^2=(a+b)\cdot (a+b)$

$=a\cdot a+a\cdot b+b\cdot a+b\cdot b$

$=a^2+2ab+b^2$

2. Binomische Formel

$(a-b)^2=(a-b)\cdot (a-b)$

$=a\cdot a+a\cdot (-b)+(-b)\cdot a+(-b)\cdot (-b)$

$=a^2-2ab+b^2$

3. Binomische Formel

$(a+b)\cdot (a-b)=a\cdot a+a\cdot (-b)+b\cdot a+b\cdot (-b)$

$=a^2-b^2$

Menü schließen